Standardization of spawn and substrate formulations for morchella mushroom cultivation - Sidra Khaliq; Tariq Mukhtar; Gulshan Irshad; Muhammad Tariq; Syed Z. Ali; Amer Mehmood; Kachu Z. Haider; Rahim U. Din; Md Arshad Ali; Chong, Khim Phin (Pakistan Journal of Phytopathology Department of Plant Pathology, University of Agriculture Faisalabad, Pakistan, 2025)
The present study evaluated various cultural media and substrate formulations to optimize the cultivation of Morchella esculenta. Three culture media, Potato Dextrose Agar (PDA), Malt Extract Agar (MEA), and Czapek-Dox Agar (CDA), were tested for mycelial growth at 25°C over 3, 5, and 7 days. PDA proved most effective, supporting the fastest and most extensive mycelial expansion (8.4 cm by day 7), followed by MEA (7.2 cm) and CDA (5.4 cm), likely due to its nutrient-rich composition. For spawn production, three cereal grains, barley, wheat, and white sorghum, were assessed over 7, 14, and 21 days. Barley supported the most vigorous growth (9.0 cm by day 21), followed by wheat (8.0 cm) and sorghum (6.0 cm), suggesting barley offers optimal nutrition and texture for spawn development. Substrate evaluations without nutrient bags involved three formulations: Compost-Potting Soil-Sand, Hardwood Chips, and Sawdust. While all supported sclerotia and pinhead formation, none produced mature fruiting bodies. Hardwood Chips showed the best early development (5 fruiting bodies), yet nutrient limitations restricted full maturation. With nutrient bags, substrate performance improved. Soil + Wheat Straw yielded 20 fruiting bodies with the fastest development. Soil + Organic Matter + Peat Moss produced the highest number of fruiting bodies (22), though no mature mushrooms were harvested. The enhanced initiation stage with nutrient supplementation highlights its importance, but the absence of full maturation across treatments suggests environmental factors or micronutrient deficiencies may be limiting. Further refinement of growth conditions and nutrient inputs is necessary for successful Morchella cultivation.